Extreme work environment and career commitment of nurses - (:unkn) unknown (Emerald Publishing Limited, 2024)
Purpose: This paper aim to analyse the motives behind the commitment of nurses to their profession despite their intense job duties during the COVID-19 pandemic. Design/methodology/approach: The empirical sample comprises of 35 semi-structured interviews...
Keywords: Enfermería; Compromiso profesional